A study of the Singapore sports council library in post-colonial and post-war Singapore, I974-20I4: Issues and challenges in the provision of information sources in sport and leisure - Lim, P.H.; Aman, M.S. (2014)
There was no known record of Sports libraries in Singapore during British (1819-1941; 1946-1959) and Japanese (1942-1945) colonial rule. After Singapore became a sovereign island city state in 1965, the government established the Singapore Sports Council (SSC) in 1973. The SSe's library, the first specialised sports library, was founded the following year. The research methodology consisted mainly of studying the Council's annual reports (1973-2012), seven published library survey responses (1975, 1983, 1989, 1993, 1996, 2000 and 2006) and 40 visits to the Library over a two-year period to physically look at its collection. The research findings suggest that there were three phases of development. The first phase is from 1974 to 1997 when the Library grew rapidly under the as part of the Information and Research Division. During the second phase of 1998 to 2010 the Library was under Management Services. It began to automate its library system by subscribing to CARL Information Management and Delivery System. During the years 2010 to April 2014 the Library was shifted to a temporary location after the National Stadium was demolished to build the Sports Hub. Its bounded serials collection was kept in a warehouse, including many books which were not accessible to users. The reconfigured Library branded as Singapore Sports Hub Library, with five times larger floor space, than the previous library, is expected to be opened at its new venue in June 2014. Recommendations were made to the staffing, collection development and the provision of services to the new Library.